Analysis of Bothrops jararacussu venomous gland transcriptome focusing on structural and functional aspects: I - gene expression profile of highly expressed phospholipases A(2) - Kashima, S.; Roberto, P. G.; Soares, A. M.; Astolfi, S.; Pereira, J. O.; Giuliati, S.; Faria, M.; Xavier, MAS; Fontes, MRM; Giglio, JR; Franca, S. C. (Elsevier B.V., 2004)
Snake venom glands are a rich source of bioactive molecules such as peptides, proteins and enzymes that show important pharmacological activity leading to in local and systemic effects as pain, edema, bleeding and muscle necrosis. Most studies on pharmacologically active peptides and proteins from snake venoms have been concerned with isolation and structure elucidation through methods of classical biochemistry. As an attempt to examine the transcripts expressed in the venom gland of Bothrops jararacussu and to unveil the toxicological and pharmacological potential of its products at the molecular level, we generated 549 expressed sequence tags (ESTs) from a directional cDNA library. Sequences obtained from single-pass sequencing of randomly selected cDNA clones could be identified by similarities searches on existing databases, resulting in 197 sequences with significant similarity to phospholipase A(2) (PLA(2)), of which 83.2% were Lys49-PLA(2) homologs (BOJU-1), 0.1% were basic Asp49-PLA(2)s (BOJU-II) and 0.6% were acidic Asp49-PLA(2)s (BOJU-III). Adjoining this very abundant class of proteins we found 88 transcripts codifying for putative sequences of metalloproteases, which after clustering and assembling resulted in three full-length sequences: BOJUMET-I, BOJUMET-II and BOJUMET-III; as well as 25 transcripts related to C-type lectin like protein including a full-length cDNA of a putative galactose binding C-type lectin and a cluster of eight serine-proteases transcripts including a full-length cDNA of a putative serine protease. Among the full-length sequenced clones we identified a nerve growth factor (Bj-NGF) with 92% identity with a human NGF (NGHUBM) and an acidic phospholipase A2 (BthA-I-PLA(2)) displaying 85-93% identity with other snake venom toxins. Genetic distance among PLA(2)s from Bothrops species were evaluated by phylogenetic analysis. Furthermore, analysis of full-length putative Lys49-PLA(2) through molecular modeling showed conserved structural domains, allowing the characterization of those proteins as group II PLA(2)s. The constructed cDNA library provides molecular clones harboring sequences that can be used to probe directly the genetic material from gland venom of other snake species. Expression of complete cDNAs or their modified derivatives will be useful for elucidation of the structure-function relationships of these toxins and peptides of biotechnological interest. (C) 2004 Elsevier SAS. All rights reserved.
Keywords: Bothrops jararacussu; snake venom gland EST's; transcriptome; gene expression; toxins; enzymes; phospholipases A(2)